2016
DOI: 10.1038/srep18423
|View full text |Cite
|
Sign up to set email alerts
|

Immune cell impact of three differently coated lipid nanocapsules: pluronic, chitosan and polyethylene glycol

Abstract: Lipid nanocapsules (NCs) represent promising tools in clinical practice for diagnosis and therapy applications. However, the NC appropriate functionalization is essential to guarantee high biocompatibility and molecule loading ability. In any medical application, the immune system-impact of differently functionalized NCs still remains to be fully understood. A comprehensive study on the action exerted on human peripheral blood mononuclear cells (PBMCs) and major immune subpopulations by three different NC coat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
48
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 83 publications
5
48
1
Order By: Relevance
“…The presence of the PEG corona at the NC surface did not result in a decrease in its level of interaction with blood cells, as indicated by similar phagocytic indices for all leukocyte types with either PLA NC or PLA-PEG NC in human blood. These findings are in agreement with a recent study where internalization of PEG-coated lipid NC by immune cells was observed at a similar frequency to Pluronic F68 or chitosan coated PLA NP(Farace et al, 2016). Interestingly, a significantly lower level of interaction of PLA-Cs NC was observed with mice than with human leukocytes in comparison with the other NC.…”
supporting
confidence: 94%
See 1 more Smart Citation
“…The presence of the PEG corona at the NC surface did not result in a decrease in its level of interaction with blood cells, as indicated by similar phagocytic indices for all leukocyte types with either PLA NC or PLA-PEG NC in human blood. These findings are in agreement with a recent study where internalization of PEG-coated lipid NC by immune cells was observed at a similar frequency to Pluronic F68 or chitosan coated PLA NP(Farace et al, 2016). Interestingly, a significantly lower level of interaction of PLA-Cs NC was observed with mice than with human leukocytes in comparison with the other NC.…”
supporting
confidence: 94%
“…Farace et al 2016 (Farace et al, 2016) found that chitosan NC aggregated upon immersion in buffer at pH 7.4. Similarly, PLA-Cs NC are likely to aggregate under physiological pH.…”
mentioning
confidence: 98%
“…Oleate seems to confer a different load and agglomeration potential, favoring cell uptake and, therefore, cytotoxicity [55]. Recently, Farace et al studied the effect of nanocapsules (PCs, 170-300 nm) coated with chitosan and pluronic PEG on peripheral blood mononuclear cells and subpopulations of T lymphocytes and monocytes which were taken as representative of the innate immune response [56]. …”
Section: Interaction Of Nanomaterials With Peripheral Mononuclear Cellsmentioning
confidence: 99%
“…Several authors have pointed out that the immune system's recognition of nanoparticles is influenced by the type of covering, the formation of the protein corona, the charge, and the functional group, among others. Since each nanomaterial has its own characteristics, it might modulate the immune system's response through several pathways [1,24,31,32]. …”
Section: Discussionmentioning
confidence: 99%